Cuba in Repertorio Americano, between nationalism and avant-garde - Vázquez, Marlene (2021)
Joaquín García Monge promoted intercultual dialogue in Latin America from Costa Rica, where the work of Martí and the intellectual production of Cuba had an important place, as well as the avant-garde youth that came to life the legacy of the Cuban hero.